Biotronik Home Monitoring® – The Benefits of Telemonitoring of Cardiovascular Implantable Electronic Devices - Łuczak, Mikołaj (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Remote patient monitoring (telemonitoring) has the potential to bring about reductions in the costs associated with caring for patients equipped with cardio-active implants. Partial replacement of classic very resource absorbance follow ups of the devices held in specialized clinics will reduce costs for patients and the healthcare system. Using BIOTRONIK Home Monitoring® system can easily detect early changes in the patient's condition associated with atrial arrhythmias, or heart failure and technical problems as compared to the conventional model of periodic visits to the clinic. This ability to early detection may significantly reduce the incidence of atrial arrhythmias and heart failure and related hospitalizations, which translates into significant cost savings.